Serum miRNA expression profiling reveals miR-486-3p may play a significant role in the development of autism by targeting ARID1B. Issue 17 (5th December 2018) - Yu, Dan; Jiao, Xueqian; Cao, Tao; Huang, Fusheng
Abstract : Recent studies have implicated microRNAs (miRNAs) in autism and have supported changes in serum miRNA expression profile. We proposed to analyze miRNA expression and its target genes related to regulatory networks in autism within a cohort of Chinese patients. The aim of this study was to explore the dysregulation of miRNAs in autism and investigate the potential mechanistic implications in the pathogenesis of autism. MiRNA was isolated from the serum samples of 20 patients with autism and 23 controls. Dysfunctional miRNAs were identified using miRNA microarray analyses. We used quantitative reverse transcription-PCR to examine the four differentially expressed miRNAs. The target gene of miR-486-3p was confirmed by luciferase assay and miRNA transfection in SH-SY5Y cell lines. A total of 77 differentially expressed miRNAs were found in the miRNA microarray analysis of two patients with autism compared with three controls. On the basis of the microarray results, quantitative reverse transcription-PCR analysis indicated that miR-557 and miR-486-3p expression levels were significantly increased ( P <0.05) in 18 patients with autism compared with 20 controls. Overexpression of miR-486-3p decreased ARID1B mRNA and protein levels ( P <0.05), whereas inhibition of miR-486-3p increased the mRNA and protein levels of ARID1B in SH-SY5Y cell lines. Luciferase activity was significantly decreased compared with the control group ( P <0.05) after cells were co-transfected with miR-486-3p mimics and ARID1B 3′-untranslated region. Our study has highlighted that miR-486-3p expression is increased in serum of patients with autism and supports that miR-486-3p inhibits the expression of ARID1B .